Reliability and validity of digital health metrics for assessing arm and hand impairments in an ataxic disorder. Issue 4 (27th February 2022) - Kanzler, Christoph M.; Lessard, Isabelle; Gassert, Roger; Brais, Bernard; Gagnon, Cynthia; Lambercy, Olivier
Abstract: Objectives: Autosomal recessive spastic ataxia of Charlevoix‐Saguenay (ARSACS) is the second most frequent recessive ataxia and commonly features reduced upper limb coordination. Sensitive outcome measures of upper limb coordination are essential to track disease progression and the effect of interventions. However, available clinical assessments are insufficient to capture behavioral variability and detailed aspects of motor control. While digital health metrics extracted from technology‐aided assessments promise more fine‐grained outcome measures, these have not been validated in ARSACS. Thus, the aim was to document the metrological properties of metrics from a technology‐aided assessment of arm and hand function in ARSACS. Methods: We relied on the Virtual Peg Insertion Test (VPIT) and used a previously established core set of 10 digital health metrics describing upper limb movement and grip force patterns during a pick‐and‐place task. We evaluated reliability, measurement error, and learning effects in 23 participants with ARSACS performing three repeated assessment sessions. In addition, we documented concurrent validity in 57 participants with ARSACS performing one session. Results: Eight metrics had excellent test–retest reliability (intraclass correlation coefficient 0.89 ± 0.08), five low measurement error (smallest real difference % 25.4 ± 5.7), and none strong learning effects (systematic change η −0.11 ± 2.5). Significant correlations ( ρ 0.39 ± 0.13) with clinical scales describing gross and fine dexterity and lower limb coordination were observed. Interpretation: This establishes eight digital health metrics as valid and robust endpoints for cross‐sectional studies and five metrics as potentially sensitive endpoints for longitudinal studies in ARSACS, thereby promising novel insights into upper limb sensorimotor control.